PERAN PEMERINTAH DESA DALAM MENDORONG PARTISIPASI POLITIK MASYARAKAT PADA PEMILU DI DESA KETAPANG KECAMATAN TANGGULANGIN - Muhammad Prayoga Arianto; Lailul Mursyidah (Journal Publicuho, 2025)
Ketapang Village was a village that was hit by the Lapindo hot mud disaster and most of the village residents moved. This has resulted in a decline in the level of community political participation, especially in elections. This research aims to encourage the role of village government in encouraging community political participation in elections in Ketapang Village. This research applies a qualitative descriptive method. Data collection methods include observation, in-depth interviews, and documentation. The research results show that the role of the Ketapang Village Government in increasing community political participation in elections in Ketapang Village, Tanggulangin District, is still not optimal.  This is evidenced by the low level of community political participation in the elections in Ketapang Village which is caused by the large number of absentee Permanent Voter Lists dominated by residents outside the village domicile.